2020
DOI: 10.1177/2192568220932168
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for the Spine Surgeon in the Age of COVID-19: Multicenter Experiences of Feasibility and Implementation Strategies

Abstract: Study design: Multicenter study. Objectives: The COVID-19 pandemic has obligated physicians to recur to additional resources and make drastic changes regarding the standard physician-patient encounter. In the last century, there has been a substantial improvement in technology, which over the years has opened the door to a new form of medical practicing known as telemedicine. Methods: Healthcare workers from three hospitals involved in the care for COVID-19 patients in the united states were invited to share t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…Based on our survey, we found that telemedicine provides significant advantages in the current socially distanced environment. Recent evidence suggests that spine telemedicine is feasible [5,11,14], but there are doubts about whether telemedicine will continue to be a viable option once shelter-in-place demands subside due to provider preferences and patient demand [15]. We found that 95.4% of our respondents required one in-person visit prior to surgery and overwhelmingly favored in-person visits, echoing the concerns over whether clinicians will continue to offer telemedicine in the future.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Based on our survey, we found that telemedicine provides significant advantages in the current socially distanced environment. Recent evidence suggests that spine telemedicine is feasible [5,11,14], but there are doubts about whether telemedicine will continue to be a viable option once shelter-in-place demands subside due to provider preferences and patient demand [15]. We found that 95.4% of our respondents required one in-person visit prior to surgery and overwhelmingly favored in-person visits, echoing the concerns over whether clinicians will continue to offer telemedicine in the future.…”
Section: Discussionmentioning
confidence: 72%
“…Telemedicine usage among spine surgeons has rapidly risen in response to the novel coronavirus (COVID-19) pandemic and social distancing directives [1][2][3][4][5][6]. In a global survey investigating the impact of COVID-19 on spine surgeons, Louie et al [1] found that 35.6% of respondents were performing the majority of appointments via telemedicine by the end of the first quarter of 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as institutions integrate telemedicine into their practices, it will be important to provide exposure to this new technology in a graduated fashion. When possible, institutional adoption of telemedicine should include training on the differences between telemedicine and in-person visits, simulated visits, exposure of house staff to telemedicine and accounting for an “adjustment phase” for new providers [ 6 , 7 , 16 ], similar to the steps taken when onboarding a new provider to the practice.…”
Section: Discussionmentioning
confidence: 99%
“…The author(s) declared no potential conflicts of interest with respect to the research, authorship, and/or publication of this article. 1 Yong Loo Lin School of Medicine, National University Singapore, Singapore…”
Section: Editors' Notementioning
confidence: 99%
“…Recently, I read with keen interest the article titled “Telemedicine for the Spine Surgeon in the Age of COVID-19: Multicenter Experiences of Feasibility and Implementation Strategies” by Franco et al 1 In their article, the authors described the experiences and salient benefits of telemedicine in spine surgery from 3 hospitals involved in the care of COVID-19 patients. They also highlight how they have adapted physical examinations to suit the nature of virtual consultation, such as replacing traditional muscle strength testing with more objective strength and functional testing using household objects, which are arguably more useful in determining which patients should undergo surgery.…”
mentioning
confidence: 99%